Partisipasi Sosial Masyarakat Dalam Pengembangan Kawasan Wisata Tongke- Tongke Kabupaten Sinjai - Firdaus Fidaus; Jamaluddin Arifin; A. Annisa Safitri (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2023)
Community social participation is participation in the development activities of an area. The purpose of this study is to analyze more deeply the supporting factors of the community in participating and what forms of participation are carried out by the community. This research is a phenomenological study using 12 informants with data collection methods using observation, interviews and documentation then analyzed descriptively qualitatively. The results of this study indicate that (1). Community supporting factors participate in the development of the Tongke-Tongke tourism area in East Sinjai District, Sinjai Regency, namely economic factors, environment, age, education and length of stay (2). Forms of Community Participation, namely participation in decision making, implementation, monitoring and utilization of results.